Diagnostic Performance of FDG-PET/CT Scan as Compared to US-Guided FNA in Prediction of Axillary Lymph Node Involvement in Breast Cancer Patients - Assi, Hazem I.; Alameh, Ibrahim A.; Khoury, Jessica; Bou Zerdan, Maroun; Akiki, Vanessa; Charafeddine, Maya; El Saheb, Ghida I.; Sukhon, Fares; Sbaity, Eman; Baydoun, Serine; Shabb, Nina; Berjawi, Ghina; et al. (Frontiers in Oncology, 2021)
Abstract The aim of this study was to evaluate the diagnostic abilities of 18F-FDG PET/non-contrast CT compared with those of US-guided FNA for axillary lymph node staging in breast cancer patients. Patients and methods: Preoperative 18F-FDG PET/non-contrast CT was performed in 268 women with breast cancer, as well as axillary lymph node dissection or sentinel lymph node biopsy. 164 patients underwent ultrasound-guided FNA, in combination with 18F-FDG PET/CT. The diagnostic performance of each modality was evaluated using histopathologic assessments as the reference standard. ROC curves were compared to evaluate the diagnostic ability of several imaging modalities. Results: Axillary 18F-FDG uptake was positive in 180 patients and 125 patients had axillary metastases according to the final pathology obtained by axillary lymph node dissection and/or sentinel lymph node dissection. 21% of patients with positive 18F-FDG uptake in the axilla had false-positive results, whereas 79% were truly positive. 88 patients had negative 18F-FDG uptake in the axilla, among which 25% were false-negative. 18F-FDG-PET/CT had a sensitivity of 86.59% in assessment of ALN metastasis with specificity of 63.46%; on the other hand, US- guided FNA had a sensitivity of 91.67% and specificity of 87.50%. Mean primary cancer size (p = 0.04) and tumor grade (p = 0.04) in combination were the only factors associated with accuracy of 18F-FDG PET/CT for detecting the metastatic axillary lymph nodes. Conclusion: The diagnostic performance of 18F-FDG PET/CT for detection of axillary node metastasis was not significantly different from that of US-guided FNA in breast cancer patients. Combining 18F-FDG PET/CT with US-guided FNA or sentinel lymph node biopsy could improve the diagnostic performance compared to 18F-FDG PET/CT alone.